Gender and Lexical Variation in Pitch, Duration, and Intensity: A Phonetic Study of Indonesian-Origin Words - Idami, Zahratul; Suhery, Dedy; Rahmadsyah, Rangkuti; Hara, Nina Tiya; Rangkuti, Ana Rahmawati (Universitas Teuku Umar, 2025)
This study investigates how gender influences suprasegmental features—specifically pitch, duration, and intensity—in the pronunciation of Indonesian-origin words. The research addresses the problem of limited phonetic studies examining gender-based acoustic variation in Indonesian, particularly in devoiced stop consonants. The objective is to analyze whether and how gender differences manifest in these prosodic elements. Using a descriptive qualitative method, data were collected from ten participants—five males and five females—from diverse ethnic backgrounds (Bataknese, Javanese, Karonese, and Melayunese), all residing in Medan, North Sumatra. Nine commonly used Indonesian-origin words were selected, and acoustic features were analyzed using PRAAT software. The results show that female speakers consistently produced higher pitch values across all words, with peaks reaching up to 499 Hz, while male speakers demonstrated lower and narrower pitch ranges, as low as 94 Hz. Duration values also varied more among female speakers, ranging from 0.097 ms to 0.469 ms, indicating more dynamic articulation patterns, although some male speakers also showed extended durations in specific contexts. Intensity levels ranged from 23 dB to 54 dB, with female speakers exhibiting greater variability in loudness—from soft to very loud—whereas male speakers maintained a more stable and moderate intensity. These findings suggest that pitch differences are primarily influenced by physiological factors such as vocal fold structure, while duration and intensity are more reflective of individual articulation style, emotional expressiveness, and speech clarity. Despite limitations in audio editing features in PRAAT, the study provides new insights into how gender and speaker identity shape suprasegmental variation in Indonesian phonetics.